1995
DOI: 10.1029/95jd01172
|View full text |Cite
|
Sign up to set email alerts
|

On the origin and nature of the interannual variability of the winter stratospheric circulation in the northern hemisphere

Abstract: During the northern hemisphere winter, the stratospheric circulation exhibits quite large interannual variability. In the present study, the nature and origin of the interannual variation in the winter stratosphere is studied with two different approaches: one is composite analysis assuming a priori four possible causes: solar activity, equatorial quasi‐biennial oscillation (QBO), volcanic aerosols, and unknown cause producing trends, while the other is an extended empirical orthogonal function analysis (E‐EOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
94
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 36 publications
12
94
0
Order By: Relevance
“…At the same time, however, the variability of the atmosphere at lower altitudes is also found to be related to the solar cycle (Labitzke and van Loon 1997;Hood et al 1993;Kodera 1995). These signals suggest the existence of an indirect effect of solar radiation by way of amplifying the small solar signal through the interaction with dynamics.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the same time, however, the variability of the atmosphere at lower altitudes is also found to be related to the solar cycle (Labitzke and van Loon 1997;Hood et al 1993;Kodera 1995). These signals suggest the existence of an indirect effect of solar radiation by way of amplifying the small solar signal through the interaction with dynamics.…”
Section: Introductionmentioning
confidence: 98%
“…The existence of the downward propagation of anomalous zonal wind is pointed out by observational studies (Kodera et al 1990, Kodera 1995. Kodera (1995) has shown that the signal due to external forcing, such as solar forcing, can be regarded as a modulation of the internal mode of variability of the atmosphere characterized by poleward and downward movement of the zonal-mean zonal wind anomaly.…”
Section: Introductionmentioning
confidence: 99%
“…The interannual variability in stratospheric circulation reflects year-to-year differences in the intraseasonal variation (including sudden warming events) and is thought to be an internal variation triggered by external forcings (Kodera 1995). For the extratropical stratosphere-troposphere coupled system, the equatorial quasi-biennial oscillation (QBO) is included as an external forcing in addition to the 11-year solar cycle, El Niñ o/Southern Oscillation, volcanic aerosols and so on, whereas tropospheric wave forcing of stratospheric circulation is included within the internal variability due to the nonlinear dynamics (Yoden 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The oscillations propagate down from the upper stratosphere and may be related to the Arctic Oscillation, which is a mode of variability that is sensitive to SC influence (e.g., Kodera [43]; Thompson [48]). …”
Section: Discussionmentioning
confidence: 99%